Comparison of activated carbons prepared by one-step and two-step chemical activation process based on cotton stalk for supercapacitors application. (15th January 2021) - Cheng, Jie; Hu, Sheng-Chun; Sun, Guo-Tao; Kang, Kang; Zhu, Ming-Qiang; Geng, Zeng-Chao
Abstract: Cotton stalk (CS) was successively treated via one-step and two-step activation process to synthesize activated carbons (ACs), which were utilized for electrode substances in the supercapacitors. The results showed that the activated carbon generated via one-step activation process at 600 °C demonstrate excellent specific surface area (1342.93 m 2 /g), which accompanied with high proportion of mesopores pore volume (97%) than those from two-step activation process. Moreover, a large specific capacitance of 338 F/g was observed in the AC that generated at the activated temperature of 600 °C via one-step activation process. The biomass-derived ACs presented an overall better electrochemistry characteristic than those from biochar-derived ACs, suggesting that the electrochemical performances of activated carbon generated from biomass-derived were better than those from biochar-derived. The data proved that the as-prepared ACs are promising materials for advanced energy storage, which is beneficial for value-added and industrial supercapacitors application of cotton stalk activated carbons. Graphical abstract: Image 1 Highlights: The cotton stalk was converted into ACs by one-step and two-step activation process. The ACs exhibited high surface areas and abundant mesopores. The excellent porous ACs were prepared by one-step activation method. Relationship between structure and capacitive performance of ACs were detected. The highest AC-based supercapacitors performance reached to 338 Fg −1 .